1997
DOI: 10.1002/(sici)1096-9063(199709)51:1<39::aid-ps611>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pesticides on species of non-target Heteroptera inhabiting cereal fields in southern England

Abstract: :The e †ects of pesticides on beneÐcial predatory arthropods have been widely studied ; this paper however deals with their e †ects on Heteroptera, an important beneÐcial insect group and food source for farmland birds. Field trials were used to evaluate pesticide e †ects under realistic conditions of application on a commercial arable farm and compared with previously published laboratory Ðndings. Fungicides were found to produce very low levels of mortality, not signiÐcantly di †erent from control treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…For example, organic fields tend to have more chick‐food insects for partridges than paired conventional fields (Moreby & Sotherton 1997). Pesticides reduced insect numbers in unsprayed headlands (Sotherton 1991; de Snoo 1999), in subfield experiments (Moreby, Sotherton & Jepson 1997), and in a range of field‐scale experiments (Holland et al . 1994).…”
Section: Discussionmentioning
confidence: 99%
“…For example, organic fields tend to have more chick‐food insects for partridges than paired conventional fields (Moreby & Sotherton 1997). Pesticides reduced insect numbers in unsprayed headlands (Sotherton 1991; de Snoo 1999), in subfield experiments (Moreby, Sotherton & Jepson 1997), and in a range of field‐scale experiments (Holland et al . 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Although species-abundance and diversity analyses were not possible, the total numbers of Heteroptera and predatory Heteroptera were 70% lower in GMHT beet than in conventional beet. Although most species of Heteroptera rely on plants for part of their diet (Southwood & Leston 1959), very few species are regarded as crop pests (Moreby et al 1997) and covariate analyses indicated that the considerably smaller weed biomass and weed-seed abundance in GMHT beet compared with the conventional treatment (see also Heard et al 2003a) may have contributed to this effect. For Leptopterna dolabrata (Miridae: Stenodemini), the presence of grass seeds, with their high nitrogen content, is important for the maturation of nymphs to successful breeding adults (McNeill 1971).…”
Section: Discussionmentioning
confidence: 99%
“…This suction-sampling technique is comparable with the conventional D-vac suction sampler and has been used widely in similar entomological field studies (e.g. Moreby et al 1997). Although extraction efficiency is always less than 100%, suction samples represent a constant proportion of the population density, thus allowing valid statistical comparisons to be made between treatments for the same habitat.…”
Section: (B) Epigeal Arthropodsmentioning
confidence: 99%
“…Such devices have been used widely in similar entomological field studies (e.g. Haughton et al 2001;Maudsley et al 1997;Moreby et al 1997) and were used for invertebrate assessments within the crop (Haughton et al 2003). Although extraction efficiency is always less than 100%, suction samples represent a consistent proportion of the population present and thus allow direct statistical comparisons of abundance between treatments for the same habitat.…”
Section: (D ) Sampling Slugs and Snailsmentioning
confidence: 99%